Cordycepin Reverses Cisplatin Resistance in Non-small Cell Lung Cancer by Activating AMPK and Inhibiting AKT Signaling Pathway - Liao, Xiao-Zhong; Gao, Ying; Zhao, Hong-Wei; Zhou, Mi; Chen, Dan-Lei; Tao, Lan-Ting; Guo, Wei; Sun, Ling-Ling; Gu, Chu-Ying; Chen, Han-Rui; Xiao, Zhi-Wei; Zhang, Jia-Xing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cisplatin (DDP) is the first line chemotherapeutic agent against lung cancer. However, the therapeutic effect of DDP loses over time due to the acquired drug resistance in NSCLC cells. In recent years, the role of the traditional Chinese medicine (TCM) cordycepin (Cor) in cancer treatment is attracting attention. However, the effects of Cor on DDP resistance in NSCLC are unclear. In the present study, we aimed to investigate the effects of Cor in combination with DDP on cell proliferation and apoptosis in NSCLC and explore possible underlying mechanisms. The cell proliferation and apoptosis were analyzed in NSCLC parental (A549) and DDP-resistant (A549DDP) cells treated with DDP alone or in combination with Cor both in vitro and in vivo. Different genes and signaling pathways were investigated between DDP-sensitive and DDP-resistant A549 cells by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. The perturbations of the MAPK and PI3K-AKT signaling pathways were evaluated by Western blot analysis. Our data showed that Cor markedly enhanced DDP inhibition on cell proliferation and promotion of apoptosis compared to DDP alone group in both A549 and A549DDP cells. The synergic actions were associated with activation of AMPK and inhibition of AKT, mTOR and downstream P709S6K, S6 phosphorylation in the AKT pathway compared with DDP alone. Collectively, combination of Cor and DDP has synergistic effect in inhibiting proliferation and promoting apoptosis of NSCLC cells in the presence or absence of DDP resistance. The antitumor activity is associated with activation of AMPK and inhibition of AKT pathway to enhance DDP inhibition on NSCLC. Our results suggested that Cor in combination with DDP could be an additional therapeutic option for the treatment of DDP-resistant NSCLC.